À propos du rôle des Juifs dans les traditions sous-jacentes aux récits de l'Invention de la Croix - Feiertag, Jean Louis (Analecta Bollandiana, 2000)
One of the most striking differences between the accounts of the Helena legend is the absence of the Jews in all of them except in those of Paulinus of Nola (Ep. 31, 5) and Ambrose (De obitu Theodosii 45 and 49). By separating Paulinus' and Ambrose's personal judgements on the Jews from the information provided by their sources, it appears that the tradition used by Paulinus had no anti-jewish tendencies and that the source used by Ambrose in all probability did not even mention the Jews. The information of Paulinus' Ep. 31, 5 (received from Melania the Elder) may not be explained by the use of a literary cliché (the Jews as guides to the Holy Land), but rather by a historical fact: jewish circles have passively accepted, or at least not denied the historical authenticity of the christian site of Golgotha, and this attitude has been changed into an active consensus by the christian tradition on the meeting of Christians and Jews in Jerusalem, which Paulinus reflects. On the contrary, the anti-jewish attitude in the Protonike and Kyriakos legends indicates that these texts probably come from Syria.